Levels of the soluble LDL receptor-relative LR11 decrease in overweight individuals with type 2 diabetes upon diet-induced weight loss. (November 2016) - Berk, Kirsten A.; Vongpromek, Ranitha; Jiang, Meizi; Schneider, Wolfgang J.; Timman, Reinier; Verhoeven, Adrie J.M.; Bujo, Hideaki; Sijbrands, Eric J.G.; Mulder, Monique T.
Abstract: Background and aims: Cardiovascular disease (CVD) is a major complication in patients with type 2 diabetes (T2D), especially in those with obesity. Plasma soluble low density lipoprotein receptor-relative with 11 ligand-binding repeats (sLR11) plays a role in the development of atherosclerosis and has been linked to the metabolism of triglyceride-rich lipoproteins, adiposity, and vascular complications in T2D. We aimed to determine the effect of diet-induced weight loss on plasma sLR11 levels in overweight and obese individuals with T2D. Methods: Plasma sLR11 levels were determined in 64 individuals with T2D and BMI >27 kg/m 2 before and after a 20-week weight loss diet. As a reference, sLR11 levels were also determined in 64 healthy, non-obese controls, matched as a group for age and sex. Results: Median plasma sLR11 levels of the T2D study-group at baseline (15.4 ng/mL (IQR 12.9–19.5)) were higher than in controls (10.2 (IQR: 8.7–12.2) ng/mL; p  = 0.001). The diet resulted in a weight loss of 9.7 ± 5.2% ( p  = 0.001) and improved CVD risk factors. sLR11 levels were reduced to 13.3 ng/mL (IQR 11.0–17.1; p  = 0.001). Changes in sLR11 levels positively associated with changes in non-HDL cholesterol (B = 1.54, R 2  = 0.17, p  = 0.001) and HbA1c (B = 0.07, R 2  = 0.11, p  = 0.007), but not with weight loss (B = 0.04, R 2  = 0.05, p  = 0.076). The changes in non-HDL cholesterol and HbA1c together explained 24% of the variance of sLR11 reduction ( p  = 0.001). Conclusions: Weight loss dieting in overweight and obese individuals with T2D resulted in a reduction in plasma sLR11 levels that was associated with improvements in lipid-profile and glycemic state. Highlights: sLR11 is associated with increased cardiovascular disease (CVD) risk and vascular complications in type 2 diabetes (T2D). Diet-induced weight loss reduced sLR11 levels in overweight and obese T2D patients. The drop in sLR11 was linked to beneficial effects on non-HDL cholesterol and HbA1c. This may contribute to the mechanism by which diet modulates CVD risk.